Climate change impacts and farmers' responses in Chilanga District, Zambia - Kinkese, Theresa (Department of Environmental and Geographical Science, 2018)
Climate change and variability are predicted to threaten agricultural production in Southern Africa. For example, Zambia's agriculture remains vulnerable to climate change and variability due to the small-scale farmers' dependence on rain-fed agriculture. Some studies in Zambia have shown the quantitative negative impacts of climate variability on agriculture; however, there is limited knowledge on how farmers perceive the impacts and adapt their agricultural systems. To fill in the knowledge gap mentioned above, the aim of the present study was to evaluate farmers' observations of climate variability impacts and their responses. The study then evaluates the integration of farmers' climate variability observations and adaptation strategies into local district plans. Such integration is deemed critical to ensure agricultural strategies promoted by extension officers are locally relevant and are adopted by the farmers. The study is based on semi-structured interviews and literature review. Thirty-one (31) farmers from Mwembeshi, Chilanga District, Zambia, participated in the study. The findings of the survey indicate that farmers in Mwembeshi are aware of their vulnerability to climate variability impacts. As a result of the observed impacts, they have developed several adaptation strategies. Through this study, extension agents were also interviewed in order find out what adaptation strategies are promoted to the farmers. The findings of the research indicate agricultural extension agents follow national agricultural adaptation strategies (top-down approach). As a result, local agricultural development plans would not specifically integrate/respond to climate variations impacts observed by the farmers. In order to engage local farmer impacts of the climate variability and their adaptation strategies into the local plans, the research suggests a more flexible (or bottom-up) approach to local development planning. Such an approach would allow the integration of local farmer observations of climate variability and their adaptation strategies into district plans. The study also found that extension agents have limited knowledge of climate variability and change, which negatively affects knowledge transfer to farmers on the subject. Therefore, training the extension officers in the subject would most likely increase farmers' knowledge on climate variability and adaptation decision.